Direct detection of RNA modifications and structure using single-molecule nanopore sequencing - William Stephenson; Roham Razaghi; Steven Busan; Kevin M. Weeks; Winston Timp; Peter Smibert (Elsevier, 2022)
Summary: Modifications are present on many classes of RNA, including tRNA, rRNA, and mRNA. These modifications modulate diverse biological processes such as genetic recoding and mRNA export and folding. In addition, modifications can be introduced to RNA molecules using chemical probing strategies that reveal RNA structure and dynamics. Many methods exist to detect RNA modifications by short-read sequencing; however, limitations on read length inherent to short-read-based methods dissociate modifications from their native context, preventing single-molecule modification analysis. Here, we demonstrate direct RNA nanopore sequencing to detect endogenous and exogenous RNA modifications on long RNAs at the single-molecule level. We detect endogenous 2'-O-methyl and base modifications across E. coli and S. cerevisiae ribosomal RNAs as shifts in current signal and dwell times distally through interactions with the helicase motor protein. We further use the 2'-hydroxyl reactive SHAPE reagent acetylimidazole to probe RNA structure at the single-molecule level with readout by direct nanopore sequencing.